2019
DOI: 10.1016/j.jvacx.2019.100035
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical role of IL-25 in ILC development and function at the lung mucosae following viral-vector vaccination

Abstract: This study demonstrates that modulation of IL-25 and IL-33 cytokines responsible for innate lymphoid cell 2 (ILC2) activation/function can differentially regulate ILC profiles at the vaccination site, in a vaccine route-dependent manner. Specifically, recombinant fowlpox (rFPV) vector-based vaccine co-expressing an adjuvant that transiently sequestered IL-25 (FPV-HIV-IL-25 binding protein), delivered intramuscularly (i.m.) was able to induce significantly lower IL-25R + ILC2-deived IL-13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…When unravelling the immune mechanisms linked to our vaccines, we have shown that IL-4R antagonist adjuvanted vaccine induce significantly reduced ILC2-derived IL-13 at the vaccination site 24 h post-delivery compared to the control 17 , responsible for the observed immune outcomes 24,26 . Recently, using range of viral vector-based vaccines we have also demonstrated that ILC-derived IL-13 is the master regulator of different ILC subsets, as well as DC activity at the early stage of vaccination, shaping the downstream adaptive immune outcomes [17][18][19][20][21]23 . Specifically, although IL-13 is known to be detrimental for high avidity T cell induction 13,15,23 , low IL-13 at the vaccination site has shown to be crucial for effective antibody differentiation/ formation 24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When unravelling the immune mechanisms linked to our vaccines, we have shown that IL-4R antagonist adjuvanted vaccine induce significantly reduced ILC2-derived IL-13 at the vaccination site 24 h post-delivery compared to the control 17 , responsible for the observed immune outcomes 24,26 . Recently, using range of viral vector-based vaccines we have also demonstrated that ILC-derived IL-13 is the master regulator of different ILC subsets, as well as DC activity at the early stage of vaccination, shaping the downstream adaptive immune outcomes [17][18][19][20][21]23 . Specifically, although IL-13 is known to be detrimental for high avidity T cell induction 13,15,23 , low IL-13 at the vaccination site has shown to be crucial for effective antibody differentiation/ formation 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the discrepancies observed in Env-specific antibody outcomes with the two vaccines, could most likely be associated with the level of IL-13 at the vaccination site (unadjuvanted > IL-4R antagonist). Interestingly, for decades different adjuvants have been used to manipulate DC activity to alter the adaptive immune outcomes [67][68][69] We have recently found that not only the co-expressed adjuvants [17][18][19] but adjuvants used with protein-based www.nature.com/scientificreports/ vaccines can significantly alter the ILC-derived IL-13 profiles at the vaccination site (S. Fig. 12), which subsequently modulate DC activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ILCs are generally divided into three distinct subsets, ILC1, ILC2, and ILC3, based on expression of cytokines, phenotypic markers, and transcription factors. Specifically, ILC2 are characterized by tissue specific surface expression of ST2/IL-33R (lung), IL-25R (muscle), or thymic stromal lymphopoietin receptor (TSLPR) (skin), and cytokines IL-4, IL-5, and IL-13, plus transcription factor GATA3 [ 24 , 25 , 26 , 27 ]. ILC1 and ILC3 are defined by the expression of NKp46, and their IFN-γ, IL-22, and IL-17A production capacity and linked to transcription factors T-bet and RORγt [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…ILC1 and ILC3 are defined by the expression of NKp46, and their IFN-γ, IL-22, and IL-17A production capacity and linked to transcription factors T-bet and RORγt [ 27 ]. However, several studies have shown that the ILC populations can be highly plastic according to different cell/tissue milieus [ 24 , 25 , 28 , 29 ]. Recent studies in our laboratory have shown that following viral vector-based vaccination, ILC2 was the major source of IL-13 at the vaccination site 24 h post-delivery [ 24 , 30 ].…”
Section: Introductionmentioning
confidence: 99%